2016
DOI: 10.1016/j.actbio.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implant topography on osseointegration under estrogen deficiency induced osteoporotic conditions: Histomorphometric, transcriptional and ultrastructural analysis

Abstract: Lower bone density, poor bone quality and osseous microstructural changes are all features characteristic of osteoporosis that may impair the osseointegration of dental implants. Using a clinically relevant trabecular bone model in the rat maxilla, we demonstrated histologically that the negative effects of surgically-induced osteoporosis on osseointegration could be ameliorated by the biomaterial's surface topography. Furthermore, gene expression analysis suggests this may be a result of enhanced osteogenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 70 publications
3
51
0
Order By: Relevance
“…The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, in 3 studies, they were placed into healed post‐extraction sockets and in 1 into the maxillary arch …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, in 3 studies, they were placed into healed post‐extraction sockets and in 1 into the maxillary arch …”
Section: Resultsmentioning
confidence: 99%
“…32 The implants were inserted mainly into the rat tibia (65.85%) or in the femur (19.5%). In 1 study, implants were placed into the medullary canal of the femur, 33 in 3 studies, they were placed into healed post-extraction sockets 29,34,35 and in 1 into the maxillary arch. 36 Rabbits were used in 10 studies (17.54%) and in 60% of these studies, the age of the animals was between 4 and 12 months.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core material, manufacturing method, and surface preparation were identical to that used for the commercially available implants available from this manufacturer. The implants had two different surface topographies as classified by Albrektsson and Wennerberg: (a) turned/machined surface or minimally rough (Ra = 0.75 µm) and (b) a moderately rough surface (Ra = 1.27 µm) that was prepared by blasting with 110‐μm‐sized aluminum oxide particles …”
Section: Methodsmentioning
confidence: 99%
“…However, given that good implant survival rates have been demonstrated with minimally rough implant surfaces, the clinical relevance of using modified implant surfaces is likely to be in sites where the quality and/or quantity of bone is less than ideal due to either systemic or local factors. Indeed, previous clinical studies have shown differences in implant survival rates between micro‐roughened and turned in low bone density sites such as in the posterior maxilla and osteoporosis, or compromised healing conditions as is encountered in smokers …”
Section: Introductionmentioning
confidence: 99%